Edipo Rey de Sófocles. Una lectura del Estásimo IV (Argos, 2025)
In the Oedipus Tyrannus Fourth Stasimon, the Chorus thinksabout Oedipus’ life, expressing both his fidelity and thankfulnessto the king. In a quiet tone, the elder men express a concentrationof concepts interesting to review. The Chorus contributes with thecompositional symmetry, since both Stasima, the Second as wellas the Forth, concern to the play but are directed to the public.Both of them look at citizens. From this point of view, we makethe philological-literary analysis of the Stasimon and relate to theco-text. At the same time, we inquire again at the thought ofSophocles.